The Multi-Loci Genotypes of the Myostatin Gene Associated with Growth Indicators of Intensively Fattened Lambs of Latvian Sheep - Ilva Trapina; Daina Kairisa; Samanta Plavina; Nikole Krasnevska; Jegors Paramonovs; Liga Senfelde; Natalia Paramonova (Animals)
Myostatin (MSTN), a member of the TGFβ superfamily, negatively affects skeletal muscle growth and controls muscle development at stages of pre-natal muscle growth. Marker-assisted selection with molecular markers of the MSTN gene can be used in animal husbandry for higher-quality and more economically profitable lambs. The study aims to identify multi-locus genotypes within the MSTN gene regions as molecular markers for fattening, feed efficiency, and carcass traits in Latvian sheep. This analysis was conducted on 76 intensively fattened male lambs representing six breeds in Latvia. Nine genotypes were identified based on four SNPs in the promoter and exon 1 regions, while six and four SNPs in introns 1 and 2 led to the formation of 14 and 10 genotypes, respectively. Six genotypes identified in the 3′UTR were significantly linked to traits such as birth weight, slaughter yield, muscle development, fat depth, average daily gain, dry matter intake, and feed efficiency. Genotypes of intron 1 were associated with slaughter yield, while genotypes of intron 2 were linked to fat depth, dry matter intake, and residual weight gain. The study concludes that MSTN gene SNPs can be used in selection to enhance sheep breeds in Latvia and improve economic outcomes for breeders.